The Disparity Of Judge's Verdict On Child Custody Decision In Aceh Sharia Court - Nasution, Adelina; Pagar, Pagar; Asmuni, Asmuni (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2022)
This article aims to explain the difference in the judge’s ruling (disparity) related to child custody (hadhānah) in the Aceh Sharia Court. This article is field research with a qualitative approach. The research method used is a normative-empirical law phenomenology that compares several judges' verdicts on hadhānah cases in the Aceh sharia court. In addition, it also describes that although Indonesia has the same Islamic legal product (KHI) but in implementation between one Judge and another can produce a different verdict. The disparity of the judge's decision that occurred in some cases in Aceh began from the legal provision that the child could not choose a father or mother if the condition had not been mumayiz. In the context of age, custody is given to his mother. In fact, there is a problem with a different verdict by KHI, that is the custody given to the father at the first stage and custody back to the mother at the appeal stage in Sharia Court. The results of the study are; First, the disparity of the judge's verdict is a reasonable situation that occurs depending on the explanation of witnesses and the fact-finding in the field. Second, the KHI format is not absolute in deciding the cases, it takes other proof so that the Judge invites expert witnesses to consider the verdict. Third, consideration of the child's mental, environmental, and condition should be a priority to decide on ideal custody.